QUALIDADE DE VIDA DE IDOSOS PARTICIPANTES DE GRUPO DE TERAPIA OCUPACIONAL - Almeida, Priscila Monteiro de (2006)
The improvement of the life quality of the senior considering a higher expectation of life aimed to know the meaning of being a senior and having quality of life for the seniors of the Grupo Metamorfose de Terapia Ocupacional through a semi-structured interview applied to ten seniors from both sexes, with ages between 60 and 82 years. The analysis of the material collected in the interviews followed the Speech of Collective Subject Method. The results indicate that the interviewees own, in general, a positive vision about the old age. About life quality, ideas emerged related to the psychological dimensions and transcendency, health, social, citizenship, economic, autonomy and family, confirming that the studied phenomena has a multidimensional character. Through the results of this study, it is suggested that, the implementation of actions turned to the quality of life of the senior, it is considered the magnitudes and differences of each specific group, not being advisable the application of standardized measures, because life aging and life quality aren't homogeneous phenomena for all of the seniors.